2009
DOI: 10.3181/0805-rm-178
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Glycyrrhizinate Protects Gastric Epithelial Cells from Hydrogen Peroxide-Induced Cell Death

Abstract: Glycyrrhiza uralensis has a potential for preventing or ameliorating gastric mucosal ulceration. To understand the molecular mechanism about the medicinal effect of G. uralensis, we isolated four single compounds from G. uralensis and one related compound and screened for the cellular protective effect against H(2)O(2)-induced damage in gastric epithelial AGS cells. Interestingly, we found that ammonium glycyrrhizinate (AG) prepared from glycyrrhizin dramatically protects AGS cells from H(2)O(2)-induced damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
(59 reference statements)
0
14
0
1
Order By: Relevance
“…9e11 Gly acts as a radical scavenger in biological systems, such as ischemiaereperfusion injury, 12,13 macrophage-like cells, 14 and gastric epithelial cells. 15 However, conflicting results have been reported regarding whether Gly itself scavenges radicals. Nagai et al reported that Gly had a potent hydroxyl radical trapping action, but did not trap superoxide anion radicals or 1,1-diphenyl-2picrylhydrazyl (DPPH).…”
Section: Introductionmentioning
confidence: 99%
“…9e11 Gly acts as a radical scavenger in biological systems, such as ischemiaereperfusion injury, 12,13 macrophage-like cells, 14 and gastric epithelial cells. 15 However, conflicting results have been reported regarding whether Gly itself scavenges radicals. Nagai et al reported that Gly had a potent hydroxyl radical trapping action, but did not trap superoxide anion radicals or 1,1-diphenyl-2picrylhydrazyl (DPPH).…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium glycyrrhizinate, prepared from glycyrrhizin, could protect gastric epithelial cells from H 2 O 2 -induced damage because it blocked the expression of genes related to apoptotic cell death (GDF15, ATF3, TNFRSF10A, and NALP1) or oxidative stress pathways (HMOX1) during damage induced by exposure to H 2 O 2 (Oh et al, 2009).…”
Section: Gastrointestinal Studiesmentioning
confidence: 99%
“…AG may directly scavenge ROS generated from hydrogen peroxide. It was also reported that AG blocked the expression of genes related to apoptotic cell death or oxidative stress pathways which was elevated in response to hydrogen peroxide treatment (Oh et al 2009). …”
Section: Discussionmentioning
confidence: 96%
“…Its antiradical activity is reported to be responsible for its antiinflammatory action (Oh et al 2009;Rackova et al 2007;Yim et al 2007). However, the effect of AG against chemically induced depletion of DA and related biochemical parameters associated with signs and symptoms of PD and drug-induced extrapyramidal side effects or symptoms remains uncertain.…”
Section: Introductionmentioning
confidence: 96%